Implementing effective injury interventions in local communities. (1st March 2011) - Layde, P; Christiansen, A; Guse, C; Peterson, D
Abstract : Community-based injury interventions that have been shown to be effective in controlled trials are often not widely implemented, resulting in unnecessary injuries. One reason for the failure to implement effective interventions is the gulf between researchers and local health authorities. Research-driven approaches to translation into practice emphasise the scientific basis of prevention by disseminating rigorously evaluated interventions from academic and governmental agencies into local communities but may suffer from a lack of community ownership which may jeopardize implementation and sustainability. Bottom-up approaches to community health improvement emphasize community leadership in identifying and developing and implementing health improvement strategies but may suffer by implementing unproven programs which address community priorities ineffectively. In this presentation we propose a model to unite the two approaches to injury intervention at the community level. To develop this Evidence-Driven Community Health Improvement Process (EDCHIP) model we started with the framework of Community Health Improvement Process, developed by the Institute of Medicine, and added explicit steps for incorporating scientific evidence into planning, implementing and evaluating community injury interventions. We discuss the model in the context of a randomised community trial of a multi-factorial intervention to reduce fall injuries in older adults. In the trial, the intervention communities are using the EDCHIP model to implement the fall prevention program while the standard communities are the traditional approach. Emergency department visits and inpatient hospitalisations for fall injuries in adults 65 years and older are the primary outcome variables.